Energy-Efficiency Maximization in Backscatter Communication-Based Non-Orthogonal Multiple Access System: Dinkelbach and Successive Convex Approximation Approaches - Dingjia Lin; Tianqi Wang; Kaidi Wang; Zhiguo Ding (IET Signal Processing)
This paper investigates a backscatter communication (BackCom) based non-orthogonal multiple access (NOMA) system in a multiple-input and single-output (MISO) scenario, where two decoding methods are deployed, including the sum-capacity approach and QR decomposition. The goal is to maximize energy efficiency (EE) through the optimization of the beamforming matrix and the reflection coefficient of the BackCom devices. Two algorithms, Dinkelbach based on penalty semidefinite relaxation (SDR) and successive convex approximation (SCA), are proposed as high-performance and low-complexity solutions, respectively. Simulation results indicate that the combination of the sum-capacity approach and Dinkelbach yields the best performance, though at the highest complexity, while the amalgamation of QR decomposition and SCA offers the lowest performance but with minimal complexity.